MENCIPTAKAN DIFERENSIASI DALAM INDUSTRI KAFE YANG KOMPETITIF DI LOMBOK - Al-Fathir Rizky Pradifa; Luqman Arziqi; Ida Puspitowati (Jurnal Serina Abdimas, 2025)
Éclair Coffee is a local cafe business located in the heart of Mataram City, carrying the concept of quality coffee combined with a creative community space. In the highly competitive cafe industry in Lombok, Éclair faces significant challenges from established brands, requiring an aggressive differentiation strategy to build a strong brand image and reach a wider market. This Community Service (PKM) activity was carried out to assist partners in formulating and implementing a differentiation strategy based on customer experience, which is crucial in industry competition The method of implementing this activity uses a descriptive qualitative approach focusing on strategic intervention and assistance directly in the field. The solution applied in this PKM began with assistance in compiling the Business Model Canvas (BMC) and SWOT Analysis. This analysis served as the basis for strategy formulation to comprehensively map the internal weaknesses and external opportunities of the business. Based on this mapping, the PKM team implemented three main differentiation strategies through the Community Involvement Program (via collaborative talkshows and workshops) and the provision of a Mini Corner Business for the empowerment and promotion of local MSMEs.The result of this PKM activity shows that Éclair Coffee successfully strengthened its Value Proposition as a center for collaboration and a creative space, which is evidenced by an increase in community interaction and the creation of a unique brand image, aligning with the theory of differentiation and positioning. This contribution positions Éclair not merely as a place to drink coffee, but as an ecosystem that grows together with the community. Éclair Coffee merupakan usaha kafe lokal yang berdiri di jantung Kota Mataram, mengusung konsep kopi berkualitas yang dipadukan dengan ruang komunitas kreatif. Dalam industri kafe yang sangat kompetitif di Lombok, Éclair menghadapi tantangan besar dari brand yang sudah mapan dan memerlukan strategi diferensiasi agresif untuk membangun brand image yang kuat serta menjangkau pasar yang lebih luas. Kegiatan Pengabdian kepada Masyarakat (PKM) ini dilaksanakan untuk mendampingi mitra dalam merumuskan dan mengimplementasikan strategi diferensiasi berbasis pengalaman pelanggan, yang krusial dalam kompetisi industry, Metode pelaksanaan kegiatan ini menggunakan pendekatan deskriptif kualitatif dengan fokus pada intervensi dan pendampingan strategis secara langsung di lapangan. Solusi yang diterapkan dalam PKM ini diwali dengan pendampingan penyusunan Business Model Canvas (BMC) dan Analisis SWOT. Analisis tersebut menjadi dasar perumusan strategi untuk memetakan kelemahan internal dan peluang eksternal bisnis secara komprehensif. Berdasarkan pemetaan ini, tim PKM mengimplementasikan tiga strategi diferensiasi utama dengan Program Keterlibatan Komunitas melalui talkshow dan workshop kolaborasi dan Penyediaan Mini Corner Business untuk pemberdayaan dan promosi UMKM lokal Hasil kegiatan PKM ini menunjukkan bahwa Éclair Coffee berhasil memperkuat Value Proposition-nya sebagai pusat kolaborasi dan ruang kreatif, yang terbukti dengan peningkatan interaksi komunitas dan menciptakan citra merek yang unik, selaras dengan teori diferensiasi dan positioning. Kontribusi ini menjadikan Éclair bukan hanya tempat ngopi, tetapi ekosistem yang tumbuh bersama masyarakat